Defining agitation in the cognitively impaired–a work in progress. (14th October 2014) - Chiu, Edmond
Abstract : The International Psychogeriatric Association (IPA) being the leading international organization in the promotion of mental health and effective treatment of mental disorders in the elderly, has a long standing enviable tradition and track record in providing leadership in this field.